A Prospective Study to Evaluate the Predictivity of Risk Malignancy Index in Adnexal Masses - Narin Yar Elmastas; Mehmet Obut; Senem Yaman Tunc (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To evaluate the efficiency of CA-125, menopausal status, ultrasound features and risk malignancy index in predicting malignancy in patients with an adnexal mass.